PENGARUH METODE READ ALOUD MELALUI CERITA BERGAMBAR UNTUK MENINGKATKAN KEMAMPUAN MENAMBAH KOSAKATA PADA SISWA KELOMPOK A - Nala Mahirotul Mufidah; Wijaya Adi Putra; Sarwo Danuji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Research entitled “The Effect of the Read Aloud Method Through Picture Stories on Improving Vocabulary Acquisition in Group A Students at Darrul Muttaqin Islamic Kindergarten.” This study aims to describe the effect of the read aloud method through picture stories on improving vocabulary building skills in group A students at Darrul Muttaqin Islamic Kindergarten. The problem to be studied is how the read aloud method activity through picture stories can influence the improvement of vocabulary building skills in group A students? The purpose of this study is to determine the effect of the read aloud method activity through picture stories on improving vocabulary building skills in group A students. The method used is a quantitative method with a pre-experimental design and using a paired sample T-test, this study analyzed the data obtained from the pre-test and post-test of the ability to increase vocabulary in group A students before and after participating in the read aloud method activity through picture stories. Based on the research and data analysis conducted by Darrul Muttaqin Islamic Kindergarten, it can be concluded that: There is a significant difference between children's vocabulary development before and after implementing the read-aloud method. The results of the Paired Sample T-Test showed a significance value of 0.000 < 0.05, thus H₁ was accepted. The read-aloud method significantly influenced the vocabulary development of Group A students at Darrul Muttaqin Islamic Kindergarten.